PENGEMBANGAN BAHAN AJAR MEMBACA UNTUK PEMBELAJAR BAHASA INDONESIA PENUTUR ASING TINGKAT DASAR - Riqoh Fariqoh (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
This research is motivated by the growing number of learners Indonesian foreign speakers, both studying in Indonesia as well as those abroad. The lack of quality teaching materials for teaching BIPA in the country make it difficult for teachers to find reference books. The purpose of this research to develop teaching materials for Indonesian read for foreign speakers. The method used in this research is the Research and Development. Based on the research results to learners Indonesian foreign speakers and also the result of judgment that the teaching material that researchers have developed enough to meet the learners, although it needs to be revised because some shortcomings such as: vocabulary and reading structures.